2023
DOI: 10.1038/s41541-023-00681-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of myocarditis and pericarditis in adolescents following COVID-19 BNT162b2 vaccination

Abstract: Myocarditis and pericarditis are frequent complications of COVID-19, but have also been reported following vaccination against COVID-19 in adolescents. To build vaccine confidence and inform policy, we characterized the incidence of myocarditis/pericarditis in adolescents following BNT162b2 vaccination and explored the association with dose and sex. We searched national and international databases for studies reporting the incidence of myocarditis/pericarditis following BNT162b2 vaccination as the primary endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…However, our findings are consistent with other studies, including one in other provinces of South Korea, reporting the similar or milder clinical course of VAM in the East Asian population, 12 14 19 As such, our study can serve as a meaningful preliminary study for further nationwide or multicountry studies of East Asian countries. We found lower incidence of VAM in South Korea compared with that of other ethnicities (3.9–16.3 cases per 100,000), 19 34 35 36 37 38 and we also found that VAM cases were less severe. The incidence of VAM in South Korea is only 3.9 cases per 100,000 (135/3,481,287, as announced by the central disease control headquarters of Korea on May 20, 2022), while more than 80% of the adolescents aged 12 to 17 years were vaccinated with the second dose.…”
Section: Discussionsupporting
confidence: 62%
“…However, our findings are consistent with other studies, including one in other provinces of South Korea, reporting the similar or milder clinical course of VAM in the East Asian population, 12 14 19 As such, our study can serve as a meaningful preliminary study for further nationwide or multicountry studies of East Asian countries. We found lower incidence of VAM in South Korea compared with that of other ethnicities (3.9–16.3 cases per 100,000), 19 34 35 36 37 38 and we also found that VAM cases were less severe. The incidence of VAM in South Korea is only 3.9 cases per 100,000 (135/3,481,287, as announced by the central disease control headquarters of Korea on May 20, 2022), while more than 80% of the adolescents aged 12 to 17 years were vaccinated with the second dose.…”
Section: Discussionsupporting
confidence: 62%
“…With the rapid rollout of COVID-19 vaccinations, numerous associated and suspected adverse events have been reported nationally and worldwide and their occurrence remains unpredictable. Literature reporting confirmed cases of pericarditis and myocarditis following SARS-CoV-2 mRNA vaccinations [21,[23][24][25][26][27][28][29][30][31]. For example, from the 27.3 million Pfizer-BioNTech (BNT162b2) doses administered in Australia to 2 January 2022, there have been 415 reports of likely myocarditis and 735 reports of likely pericarditis and that from the 1.8 million Moderna (mRNA-1273) doses administered in Australia to 2 January 2022, there have been 40 reports of likely myocarditis and 52 reports of likely pericarditis (COVID-19 vaccine weekly safety report -06-01-2022 | Therapeutic Goods Administration (TGA); accessed on 07.01.2022).…”
Section: Introductionmentioning
confidence: 81%
“…The focal/diffuse degrees of myocardial inflammation determine the severity of symptoms in patients with myocarditis and the fulminant myocarditis cases predominantly progress with elevated serum cardiac troponins [8][9][10][11][12]. Cardiovascular complications have been described in many COVID-19 patients and myocarditis (from subclinical myocardial injury to fulminant lethal myocarditis) has been proposed to account for a small fraction of cardiac injury among patients infected with SARS-CoV-2 [13][14][15][16][17][18][19][20][21]. (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding vaccination, myocarditis following vaccination has been reported, with an incidence of myocarditis/pericarditis of 4.5 per 100,000 vaccinations across all doses [ 110 ]. Our review revealed that most cases of fulminant myocarditis caused by COVID-19 did not receive vaccination; however, vaccination's number was limited, with the accumulation of more findings being expected in the future.…”
Section: Discussionmentioning
confidence: 99%